THE EFFECT OF THE PROPORTION OF JACKFRUIT (Artocarpus heterophyllus) SEED FLOUR AND THE ADDITION OF EGGS ON THE CHARACTERISTICS OF DRY NOODLES - Nurida Tri Novita; Ulya Sarofa; Sri Winarti (Jurnal Pangan dan Agroindustri, 2023)
Jackfruit seed flour (Artocarpus heterophyllus) can be used as a substitute for wheat flour in noodles production due to its high starch content and nutritional value. In addition, carrot flour is another ingredient that can be used in the production of dry noodles. The aim of this study was to determine the effect of the proportion of wheat flour, jackfruit seed flour and carrot flour, together with the supply of eggs, on the quality of the dry noodles produced. The experimental design used was Completely Randomized Design with two factors and three replications. Factor I was the ratio of wheat flour: jackfruit seed flour: carrot flour (90:5:5, 80:15:5, 70:25:5). Factor II was the addition of egg (5%, 10% and 15%). The best treatment was dry noodles made of 90% wheat flour: 5% jackfruit seed flour: 5% carrot flour and 15% egg addition, which gave the results of moisture content 7.71%, ash content 2.34%, protein content 10.68%, starch content 64.18%, amylose content 24.29%, rehydration power 55.66%, cooking loss 6.07%, elasticity 8.17%; favourability of colour, taste, aroma, texture 3.52, 3.44, 3.40, 3.48 (like).